Un análisis de los estudios acerca de las memorias de sostenibilidad en Latinoamérica - Sepúlveda Alzate, Yully Marcela; Valero Zapata, Gloria Milena; Bonilla Gómez, Martha Janeth (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
The purpose of this document is initially related to the identification of academic publications on sustainability reports, in particular those that link the referents of the Global Reporting Initiative [GRI] and which are intended to study business contexts in Latin America, for later Characterize the publications found. For this purpose, 18 articles published between 2006 and 2016 were collected in the databases of EBSCO, JSTOR and ScienceDirect. The research developed is quantitative and qualitative with a descriptive approach, firstly, quantitative because it makes use of bibliometric techniques that allow to determine where the literature focuses in this field and, qualitatively because it is based on a review of content analysis. The results indicate that most of the studies have focused on evaluating the use of sustainability reports as a management reporting tool, mainly considering the number of indicators, the model chosen or adapted and the periodicity and depth of the information.

El propósito del presente documento es, en primer lugar, identificar las publicaciones académicas sobre las memorias de sostenibilidad, en particular, las que vinculan los referentes del Global Reporting Initiative (GRI) y que tienen como objeto de estudio los contextos empresariales en Latinoamérica, para, en segundo lugar, caracterizar las publicaciones encontradas. Con ese propósito, se recolectaron 18 artículos publicados entre los años 2006 y 2016 en las bases de datos de EBSCO, JSTOR y Science Direct. La investigación desarrollada es cuantitativa y cualitativa con un enfoque descriptivo. Es de carácter cuantitativo, en la medida que hace uso de técnicas bibliométricas que permiten determinar hacia dónde se enfoca la literatura en este campo, y, a la vez, de carácter cualitativo, pues se basa en una revisión de análisis de contenido. Los resultados indican que la mayoría de los estudios se han concentrado en evaluar el uso de los informes de sostenibilidad como herramienta de informe de gestión considerando principalmente la cantidad de indicadores, el modelo escogido o adaptado, y la periodicidad y la profundidad de la información.
An analysis of the studies about sustainability reports in Latin America
Keywords: Global Reporting Initiative (GRI); Memorias de sostenibilidad; Latinoamérica; Publicaciones académicas; https://purl.org/pe-repo/ocde/ford#5.02.04